2018
DOI: 10.1007/s12217-017-9580-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Statoliths Displacement in Chara Rhizoids for Validating the Microgravity-Simulation Quality of Clinorotation Modes

Abstract: In single-celled rhizoids of the green algae Chara, positively gravitropic growth is governed by statoliths kept in a dynamically stable position 10-25 μm above the cell tip by a complex interaction of gravity and actomyosin forces. Any deviation of the tube-like cells from the tip-downward orientation causes statoliths to sediment onto the gravisensitive subapical cell flank which initiates a gravitropic curvature response. Microgravity experiments have shown that abolishing the net tip-directed gravity force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Organs and cells, which deflect the axis for some distance, will undergo centrifugal forces. A comparison of results from flight experiments and clinorotation with unicellular and multicellular organisms and tissue cultures showed that the fast clinostat is a valuable tool for evaluating an organism's sensitivity to altered gravity [8,9,37]. The absolute magnitude of the vector is incidentally preserved, consequently, the environmental properties are not changed.…”
Section: Short Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Organs and cells, which deflect the axis for some distance, will undergo centrifugal forces. A comparison of results from flight experiments and clinorotation with unicellular and multicellular organisms and tissue cultures showed that the fast clinostat is a valuable tool for evaluating an organism's sensitivity to altered gravity [8,9,37]. The absolute magnitude of the vector is incidentally preserved, consequently, the environmental properties are not changed.…”
Section: Short Overviewmentioning
confidence: 99%
“…For instance, the certain similarity of data on activation or inhibition of gene expression and protein synthesis associated with cell wall remodeling detected both in A. thaliana seedlings grown in real microgravity [38][39][40] and under 3-D clinorotation [41], as well as loosening and thinning of cell walls in microgravity and under clinostation can be explained in the light of biochemical data on quantitative and qualitative changes in the composition of poly-and monosaccharides [42,43]. A fast-rotating 2-D clinostat is also considered to be an efficient tool for studying the plant responses to simulated microgravity [8,15]. Changes in gene expression in roots of 5-day old A. thaliana seedlings as well as in the location of amyloplasts-statoliths in cap statocytes after 3 min and 6 min of fast 2-D clinirotation were described [15].…”
Section: Short Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore recommended to perform comparative studies due to the different working principles of the RPM and the clinostat. Furthermore, the quality of simulation should be validated under real microgravity (e.g., in space) [72].…”
Section: Experimental Approaches To Alter the Influence Of Gravity Onmentioning
confidence: 99%